2020
DOI: 10.3390/microorganisms8040579
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Microbiological Safety of Wooden Cutting Boards Used for Meat Processing in Hong Kong’s Wet Markets: A Focus on Food-Contact Surfaces, Cross-Contamination and the Efficacy of Traditional Hygiene Practices

Abstract: Hong Kong's wet markets play a crucial role in the country's supply of safe, fresh meat to satisfy the dietary needs of its population. Whilst food safety regulations have been introduced over the past few years to maintain the microbial safety of foods sold from these wet markets, it remains unclear whether the hygiene maintenance that is performed on the wooden cutting boards used for meat-processing is effective. In fact, hygiene maintenance may often be overlooked, and hygiene standards may be insufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 56 publications
0
18
0
3
Order By: Relevance
“…Cross‐contamination and bacterial growth are the two major concerns. Hands and utensils, as well as other food contact surfaces in kitchens, have repeatedly been reported as contamination sources based on several recent studies (Dantas et al., 2018; Habib et al., 2020; Rossi, Beilke, & Barreto, 2018; Sekoai et al., 2020). Poor food handling and hygiene practices further increase the risk of cross‐contamination.…”
Section: Contamination Sourcesmentioning
confidence: 98%
“…Cross‐contamination and bacterial growth are the two major concerns. Hands and utensils, as well as other food contact surfaces in kitchens, have repeatedly been reported as contamination sources based on several recent studies (Dantas et al., 2018; Habib et al., 2020; Rossi, Beilke, & Barreto, 2018; Sekoai et al., 2020). Poor food handling and hygiene practices further increase the risk of cross‐contamination.…”
Section: Contamination Sourcesmentioning
confidence: 98%
“…The finding of foodborne and non-foodborne pathogens in wet market cutting board settings should be considered an alarming indicator of poor hygienic conditions. Recent studies have indicated that poor hygiene practices at wet markets may have exposed cutting boards to spoilage and pathogenic surface contamination [ 5 , 19 ]. Regular surface hygiene of such wet market cutting boards may be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm detachment can arise at different stages of the biofilm formation dynamic. In the case of the surface microcosm of cutting boards, it may lead to the release and transfer of bacterial cells onto the foods being processed [ 19 ]. The wooden cutting board surface can be described as a porous material with hydrophilic properties that can provide a suitable environment conducive to the harboring, persistence and proliferation of spoilage and diverse pathogenic organisms [ 9 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eating wild animals is a symbol of wealth, and their meat is perceived to be more natural and nutritious than meat from farmed animals, and is also an ingredient in traditional medicines (9). Wet markets are often characterized by poor hygiene (10,11) and the presence of live animals kept in crowded conditions. Together with the difficulty of hygienically selling food in such environments, another risk factor for EZDs is the largely undescribed virus diversity that can been found in some wildlife orders, such as bats, rodents and primates (12).…”
Section: Wet Markets and Other Live Animal Marketsmentioning
confidence: 99%